Ecotourism Governance Pada Pembangunan Infrastruktur di Kawasan Ekowisata Pulau Kapoposang - amalia, amalia; Armin, Armin; Irawan, Andi Lukman (LP2M IAIN Palopo, 2024)
Ecotourism represents a form of development on tourism that focuses on environmental considerations. Activities within the framework of ecotourism prioritize environmental sustainability, especially in areas dedicated to conservation. This study aims to delve into the principles governing ecotourism development and assess their applicability to the development of the infrastructure within the Kapoposang Island Ecotourism Area in the Pangkajene and Islands District. The focus lies on the permit’s aspect, which holds significance as a foundational element of ecotourism governance. The issuance of licenses serves as a gateway to understanding the dynamics of interest between political figures and the private sector in the development of the infrastructure. The primary objective is to provide an initial overview of the development of the infrastructure in the Kapoposang Island Ecotourism Area, laying the groundwork for subsequent research on political, ecological, and tourism-related aspects. Using a qualitative desk research method, the research reveals that there are issues with permits for development of the infrastructure, showcasing indications of both ecological and political concerns.